Obstacles to the transition from the unified accounting system to the international accounting standards in the banking sector in the Kurdistan Region / Iraq (An empirical study of views Preparers of financial statements in banks & And observers in the Ba - المدرس المساعد. أردالن اسماعيل حامد; األستاذ المساعد الدكتور .باسمة فالح النعيمي; المدرس المساعد. مالك محمد توفيق ق (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
This research aims to study the obstacles of the transition from the unified accounting system to the international accounting standards in the banking sector and to reach the most important means that contribute to overcome these obstacles and also to know the importance of the application of international accounting standards. The research sample consists of a simple random sample which is (50) fifty of the preparers of financial statements and observers in the Banking Control Department of the Central Bank / Erbil. To achieve the research objective, t-test one sample, arithmetic mean, standard deviation and coefficient of variation were applied using SPSS. The results of the research through statistical analysis showed that there are a number of obstacles that limit the application of international accounting standards in banks operating in the Kurdistan Region of Iraq / Erbil, and also the results of the research showed a set of important means to overcome these obstacles.